The Principle of Contradiction and Symbolic Logic. Issue 2 (2nd April 2020) - Łukasiewicz, Jan; Trybus, Adam; Linsky, Bernard
Abstract : This is the first English translation directly based on the original Polish 'Zasada sprzeczności a logika symboliczna', the appendix on symbolic logic of Jan Łukasiewicz's 1910 book O zasadzie sprzeczności u Arytotelesa (On the Principle of Contradiction in Aristotle).